Analisis Keuntungan dan Penugasan dengan Metode Simpleks dan Metode Hungarian (Studi Kasus UMKM Nasi Goreng Kencur) - Saeful Jamal; Rianita Puspa Sari (Jurnal Serambi Engineering, 2022)
MSME Nasi Goreng Kencur is one of the developing MSMEs. With a variety of products for sale. Of the various variants that are sold, of course, they have different advantages. So we need a problem solving tool to find out which product has the maximum benefit. Research is able to find out how feasible and optimal solutions are from various problem models. Implementation of operational research on the completion of the case study in Nasi Goreng Kencur SMEs, to obtain optimal benefits. This research was conducted in 2022 using the interview method and direct observation, where MSME owners become the data source for conducting research. To optimize the profit can be solved by using the Integer Linear Programming problem model using the Simplex method. Then for the assignment analysis at the Nasi Goreng Kencur SMEs using the Hungarian method. In the data processing that is carried out using these two models, manual data processing is carried out, and calculations using POM-QM software. So that the results of the study become more accurate, because in addition to using manual calculations. Calculations are also used using the POM-QM application.